Chronic ethanol administration exacerbates memory loss by altering N6-methyladenosine-mediated epigenetic signaling - Liao, Yuanhang; Xu, Fu; Yan, Yuqing; Zhou, Sicheng; Liu, Na; Dou, Baomin; Srinivasan, Nivetha; Wang, Weizheng; Zhu, Xiongwei; Ye, Jianghong; Xu, Ying (Frontiers in Immunology, 2025)
BackgroundChronic alcohol use disorder (AUD) is recognized as one of the most critical risk factors for the progression of Alzheimer’s disease (AD). Epigenetic and neuroimmune alterations are closely associated with the development of memory impairment related to AUD and AD.MethodsAdult APP/PS1 transgenic mice received intermittently intraperitoneal injections of ethanol (EtOH, 2.5 g/kg, i.p.) or vehicle with two “drug” treatment days, and one and two “drug-free” days every 7 days for 10 weeks. The novel object recognition (NOR) and Y-maze tests were performed to determine whether chronic ethanol treatment exacerbated memory impairment in these mice. The brain tissues were collected for pathological changes through MeRIP/RNA-sequence analyses and molecular biological assays.ResultsThe results suggested that chronic intermittent ethanol (CIE) treatment for 10 weeks exacerbated sporadic and spatial memory deficits in NOR and Y-maze tests in the APP/PS1 mice. The pathological assays revealed that CIE procedure increased Aβ plaque burden in the brain of the AD mice, which were consistent with memory behavioral deficits. The subsequent MeRIP/RNA sequence analyses showed that two genes, e.g. Rbm15b and Hnrnpa2b1, were related to N6-methyladenosine (m6A) methylation that plays an important role in the development of memory loss. These results were further supported by molecular biological and mRNA-microRNA-lncRNA ceRNA network analyses that demonstrated that the increased Rbm15b and decreased Hnrnpa2b1 were involved in synaptic dysfunction and neuroinflammation in CIE-induced memory impairment in these AD mice.ConclusionsThe conclusion is drawn that m6A mediated epigenetic dysfunction and immune cells infiltration participate in chronic alcohol use disorder related memory loss in AD mice.